Pembelajaran Bahasa Arab di Perguruan Tinggi dalam Perspektif Ilmu Linguistik Modern - Hasanuddin Harahap (April & October, 2026)
Arabic language learning in higher education involves a high level of complexity, as it is not solely aimed at developing communicative competence but also serves as a medium for academic development and the deepening of Islamic studies. Therefore, a strong theoretical foundation is required to ensure that the learning process is systematic and effective. Modern linguistics offers a relevant conceptual framework for analyzing language structure, meaning, and use within the context of instruction. This study aims to examine Arabic language learning in higher education from the perspective of modern linguistics, particularly in relation to phonology, morphology, syntax, semantics, and pragmatics. This research employs a qualitative approach using library research, involving the analysis of books, scholarly articles, and other relevant sources. The findings indicate that the application of modern linguistic perspectives contributes significantly to the design of instructional materials, the selection of teaching methods, and the evaluation of Arabic language learning in higher education. Accordingly, the integration of modern linguistics plays an important role in improving the quality and effectiveness of Arabic language instruction at the tertiary level.